2019
DOI: 10.1039/c9ra04624k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acid and phosphate on arsenic solidification in a phosphogypsum-based cement backfill process

Abstract: Phosphogypsum (PG) produced during phosphoric acid production contains significant amounts of arsenic and can potentially cause adverse environmental and health effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The phosphogypsum-based cementitious material prepared based on JISCO slag not only makes full use of phosphogypsum, but also saves the filling cost of Jinchuan mine filling-method mining. The filling method is to backfill these wastes into the goaf, which not only treats the waste, which reduces pollution, but also reduces the probability of surface subsidence caused by mining (Min et al, 2019;Yin et al, 2019;Zhou et al, 2020). Since mining is going on all the time, it cannot be suspended due to the need for backfilling, so the backfilled body needs to have a certain strength at an early stage to avoid taking up time.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphogypsum-based cementitious material prepared based on JISCO slag not only makes full use of phosphogypsum, but also saves the filling cost of Jinchuan mine filling-method mining. The filling method is to backfill these wastes into the goaf, which not only treats the waste, which reduces pollution, but also reduces the probability of surface subsidence caused by mining (Min et al, 2019;Yin et al, 2019;Zhou et al, 2020). Since mining is going on all the time, it cannot be suspended due to the need for backfilling, so the backfilled body needs to have a certain strength at an early stage to avoid taking up time.…”
Section: Introductionmentioning
confidence: 99%
“…Although the treatment of a PG backfill involves, essentially, the dumping of PG into the underground goaf [ 12 ], the impact of toxic and hazardous substances precipitated from the backfilling body on the underground environment limits the application of phosphogypsum backfilling (PGB) technology. Yin et al [ 13 ] found that the PG generated during phosphoric acid production contains high levels of arsenic (As), resulting in adverse effects on the surrounding environment, as well as on human health when PG is stacked or handled. Chen et al [ 14 , 15 , 16 , 17 , 18 ] conducted toxic leaching tests on PGB specimens and observed precipitations of small amounts of phosphorus, fluorine, and other elements from PG even under the action of cement curing.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the toxicity of arsenic, solidi cation/stabilization (S/S) technology is always applied to dispose arsenic-bearing waste by restricting the mobility of As atoms. Several methods have been proposed to reduce arsenic contamination, such as cement solidi cation (Kundu and Gupta 2008;Yin et al 2019;Yoon et al 2010), geopolymer solidi cation (Shi et al 2017;Xu et al 2006) and vitri cation solidi cation (Shi et al 2015; Zhao et al 2015;Zhao et al 2016). As for the cement solidi cation method, arsenic atoms can be immobilized by three ways: Firstly, arsenic-bearing wastes can be enwrapped by cement (Liu et al 2018); Secondly, arsenic can react with cement and form insoluble calcium-arsenic compounds (Vandecasteele et al 2002), such as Ca 3 (AsO 4 ) 2 and CaHAsO 3 ; Thirdly, arsenic can be absorbed onto the surface of calcium silicate hydrate (C-S-H) (Li et al 2018).…”
Section: Introductionmentioning
confidence: 99%